2011
DOI: 10.1016/j.ajpath.2011.01.033
|View full text |Cite
|
Sign up to set email alerts
|

CCN3 Impairs Osteoblast and Stimulates Osteoclast Differentiation to Favor Breast Cancer Metastasis to Bone

Abstract: Bone is a preferred site for breast cancer metastasis, causing pain, fractures, spinal cord compressions, and hypercalcemia, all of which can significantly diminish the patient's quality of life. We identified CCN3 as a novel factor that is highly expressed in bone metastatic breast cancer cells from a xenograft mouse model and in bone metastatic lesions from patients with breast cancer. We demonstrate that CCN3 overexpression enhances the ability of weakly bone metastatic breast cancer cells to colonize and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 66 publications
3
44
2
Order By: Relevance
“…Besides participating in the growth and prognosis, NOV also exerted effects on the adhesion, migration and invasion of tumor cells (7). Previous studies indicated that NOV activated pI3K/aKT and NF-κB signaling pathways by combining with αvβ3 integrin receptor, thus promoting the transcription and expression of transfer relevant factors (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides participating in the growth and prognosis, NOV also exerted effects on the adhesion, migration and invasion of tumor cells (7). Previous studies indicated that NOV activated pI3K/aKT and NF-κB signaling pathways by combining with αvβ3 integrin receptor, thus promoting the transcription and expression of transfer relevant factors (37).…”
Section: Discussionmentioning
confidence: 99%
“…The CCN genes encode secreted proteins of 35-48 kDa associated with the extracellular matrix (ECM) and cell membrane, which are involved in the regulation of various cell functions such as proliferation, differentiation, migration, attachment, angiogenesis and tumorigenesis (6). These genes are expressed in all derivatives of the three embryonic sheets and are involved in the development of kidney, nervous system, muscle, bone marrow, cartilage and bone (7).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that metastases do not randomly target distant organs, but preferentially arise in those that offer the disseminated cancer cell an appropriate environment in which to grow or that express molecules supporting tumor cell homing. Recent studies demonstrate that the expression of specific molecules, including chemokine receptors as well as claudin-2, CCN3, and tenascin-C, correlate with and/or enhance metastasis to distinct sites (119,(136)(137)(138). The chemokine CXCL12 is expressed in bone marrow, and expression of its cognate receptor CXCR4 on breast tumor cells is correlated with an increased risk of metastasis to bone (139).…”
Section: Differential Preference For Sites Of Metastasesmentioning
confidence: 99%
“…Several signalling pathways in osteoclast precursors have been implicated in these effects, including calcium signalling, NFATc1 activation and MAPKs ERK1/2 and p38 (159,160). Tumour-produced CCN3 was demonstrated to stimulate osteoclast formation from RANKL-primed osteoclast precursors (147). These effects can be relevant to the propensity of cancer cells to metastasize to bone sites undergoing active bone remodelling, and thus containing increased numbers of RANKL-primed osteoclast precursors.…”
Section: Stimulation Of Osteoclasts By Breast Cancer Cellsmentioning
confidence: 99%
“…Moreover, under the influence of breast cancer cells, undifferentiated osteoblasts express higher levels of RANKL and lower OPG, resulting in an increase in osteoblast-mediated osteoclastogenesis (20), an effect that was reversed when osteoblastic cultures were treated with the inhibitors of -secretase -an enzyme implicated in Notch signalling (20,136). One of the mediators of these changes was shown to be the tumour-overexpressed CCN3, that can inhibit osteoblast differentiation and shift the RANKL/OPG ratio to favour osteolysis (147). Another osteoblast-produced osteoclastogenic factor, MCSF, has also been implicated in breast cancer metastases to bone (148).…”
Section: Contribution Of Osteoblasts To the Creation Of An Osteolyticmentioning
confidence: 99%